Germ cell tumor of anterior mediastinum: A rare case in young adult - Saurav Kumar; Raghvendra Gumashta (Wolters Kluwer Medknow Publications, 2021)
A 30-year-old diabetic male, urban resident, nonsmoker with Karnofsky performance score 80 was diagnosed with germ cell tumor of 13 cm × 9 cm with Stage I at right anterosuperior mediastinum after short duration of cough and hemoptysis. He did not have any difficulty in breathing or weight loss. The effort tolerance of the patient was up to four floors. The case received VIP-based chemotherapy with etoposide, ifosfamide, and cisplatin at a center of excellence. Thereafter, the surgical excision of the solid mass may be the optional line of treatment.